2020
DOI: 10.1177/2333794x20954332
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Response to Two Formulas in Infants with Parent-Reported Signs of Formula Intolerance: A Multi-Country, Double-Blind, Randomized Trial

Abstract: Background: Signs of feeding intolerance are common in formula-fed infants. We evaluated the clinical response to a partially hydrolyzed 100% whey protein formula with high sn-2 palmitate and reduced lactose (FA) and to an alpha-lactalbumin-enriched whey-predominant intact protein formula with full lactose (FB) in healthy full-term infants with parent-reported signs of feeding intolerance. Methods: In a double-blind, parallel-group trial in 6 Asian study centers, exclusively formula-fed infants aged 30 to 90 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…Alpha-lactalbumin improves formula digestion tolerability (29,31). Hydrolyzed proteins and alpha-lactalbumin reduce regurgitation in infants (29,31,(38)(39)(40)(41). The whey predominance of the SF likely further contributes, as gastric emptying of whey protein is faster than casein (42).…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-lactalbumin improves formula digestion tolerability (29,31). Hydrolyzed proteins and alpha-lactalbumin reduce regurgitation in infants (29,31,(38)(39)(40)(41). The whey predominance of the SF likely further contributes, as gastric emptying of whey protein is faster than casein (42).…”
Section: Discussionmentioning
confidence: 99%
“…Comparable results were found in the study by Wu and colleagues that showed no significant gastrointestinal tolerance difference among healthy infants who consumed either a formula based on hydrolysed whey protein combined with intact casein protein-or intact protein-based formula or were breastfed (21). Vivatvakin et al who studied 256 healthy infants also found no difference in the mean scores of IGSQ between infants fed with a pHF or an IPF, while lower mean total scores were observed with increasing age of the infants (26). As the control groups of the abovementioned studies showed similar findings as the test products, this might indicate that the improvement shown over time is not related to the formulas, but that other factors played a role.…”
Section: Discussionmentioning
confidence: 85%
“…The results of our study align with those from a recently published, prospective, randomized trial that reported the safety and tolerability of an extensively hydrolyzed, whey-protein infant formula derived from non-porcine enzymes in infants with CMA 16 and other studies of partially hydrolyzed whey-based formulas in older infants. 17 - 20 …”
Section: Discussionmentioning
confidence: 99%